Теоретическое оформление консерватизма и превращение его в политическую идеологию (Պահպանողականության տեսական ձևավորման և քաղաքական գաղափարախոսության վերափոխման գործընթացը) - Կարիպով, Բալտաշ (YSU Journal of International Affairs, 2015)
In this paper we show that conservatism is extremely broad, multifaceted concept that includes many levels of meaning, some of which have existed throughout the development of the entire human civilization, and some arose under the influence of specific historical events. The highest form of manifestation of this phenomenon is the presence in the heart of any civilization, a universal mechanism for performing the functions of experience in the form of specific information, transferring it from the present to future generations, as well as the perception of new information and adaptation to it, which can be characterized as conservative.
Keywords: traditionalism, conservatism hierarchy, conservative reformation, conservative ideology